The impact of endometriosis towards the severity of anemia - Nurjanah, Salsa Evva; Ningrom, Ira Citra; Purbowati, Mustika Ratnaningsih; Agatri, Norina; Poernomo, Megawati Al’badly Ponco Dewi; Marlina, Dina; Utomo, Aditya; Amri, Beni Samsul (PT WIM Solusi Prima, 2025)
The purpose of this study was to investigate the relationship between endometriosis and anemia severity, along with other potential contributing factors. The study was conducted at Margono Hospital in Indonesia and involved patients with endometriosis who were enrolled from 2020 to 2024. Inclusion and exclusion criteria were applied, and statistical analyses, including odds ratios and prevalence ratios, were performed. The analysis revealed that women of reproductive age were significantly more likely to develop endometriosis, with an odds ratio of 3.033 [95% CI 1.703-5.403, p<0.001]. Increasing age contributed 0.9% to the likelihood of endometriosis, and parity was significantly associated with endometriosis, with nulliparous women having an odds ratio of 11.883 [95% CI 2.103-67.163, p<0.001]. No significant correlation was found between anemia severity and endometriosis, though moderate anemia was most likely in the case group [OR 0.744, 95% CI 0.520-1.063, p=0.613]. Although endometriosis did not significantly affect anemia severity in our study, further research is needed to explore the molecular impact of different types of endometriosis on erythropoiesis.